Novel Therapies Boosting T Cell Immunity in Epstein Barr Virus-Associated Nasopharyngeal Carcinoma - Sarah Renaud; Anthony Lefebvre; Serge Mordon; Olivier Moralès; Nadira Delhem (International Journal of Molecular Sciences, 2020)
Nasopharyngeal carcinoma (NPC) is a malignant tumour of the head and neck affecting localised regions of the world, with the highest rates described in Southeast Asia, Northern Africa, and Greenland. Its high morbidity rate is linked to both late-stage diagnosis and unresponsiveness to conventional anti-cancer treatments. Multiple aetiological factors have been described including environmental factors, genetics, and viral factors (Epstein Barr Virus, EBV), making NPC treatment that much more complex. The most common forms of NPCs are those that originate from the epithelial tissue lining the nasopharynx and are often linked to EBV infection. Indeed, they represent 75–95% of NPCs in the low-risk populations and almost 100% of NPCs in high-risk populations. Although conventional surgery has been improved with nasopharyngectomy’s being carried out using more sophisticated surgical equipment for better tumour resection, recent findings in the tumour microenvironment have led to novel treatment options including immunotherapies and photodynamic therapy, able to target the tumour and improve the immune system. This review provides an update on the disease’s aetiology and the future of NPC treatments with a focus on therapies activating T cell immunity.